2017
DOI: 10.1186/s12978-016-0262-5
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of women’s and health providers’ attitudes and acceptability of mistreatment during childbirth in health facilities in Guinea

Abstract: BackgroundReducing maternal morbidity and mortality remains a key health challenge in Guinea. Anecdotal evidence suggests that women in Guinea are subjected to mistreatment during childbirth in health facilities, but limited research exists on this topic. This study was conducted to better understand the social norms and the acceptability of four scenarios of mistreatment during childbirth, from the perspectives of women and service providers.MethodsThis study used qualitative methods including in-depth interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 12 publications
6
74
0
4
Order By: Relevance
“…Pinching or slapping was acceptable for women and providers if it was used for encouragement or for their sake. These findings on conditions where mistreatment may be acceptable are in accordance similar findings in West Africa (Guinea and Ghana) where these type of mistreatment behaviors were not acceptable for most women unless used to save the life of the woman [17,21]. Furthermore, in Nigeria and Ghana [19,21] some women and providers considered these mistreatment behaviors as appropriate and acceptable measures to gain compliance from the woman, correct perceived "disobediences", and ensure a good outcome for the baby.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Pinching or slapping was acceptable for women and providers if it was used for encouragement or for their sake. These findings on conditions where mistreatment may be acceptable are in accordance similar findings in West Africa (Guinea and Ghana) where these type of mistreatment behaviors were not acceptable for most women unless used to save the life of the woman [17,21]. Furthermore, in Nigeria and Ghana [19,21] some women and providers considered these mistreatment behaviors as appropriate and acceptable measures to gain compliance from the woman, correct perceived "disobediences", and ensure a good outcome for the baby.…”
Section: Discussionsupporting
confidence: 82%
“…The study used a mixedmethods design to understand and measure the mistreatment of women during childbirth in Myanmar, Nigeria, Ghana and Guinea. In the first phase, formative qualitative research was conducted to understand women's and providers' experiences and acceptability of mistreatment during childbirth [16][17][18][19][20][21]. The formative findings and systematic review [15] were used to inform the development of two measurement tools in the second phase (direct observations of labor and childbirth) and a community-based survey with women during the postpartum period in the same settings [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…6,8,21 Other study sites in this WHO-led multi-country study (Nigeria and Guinea) have revealed similar experiences of mistreatment in health facilities. 22,23 Such mistreatment may have negative effects on future maternal health-seeking behaviour and choices regarding facility-based childbirth. A recent systematic review determined the existence of a wide range of disrespectful and abusive treatment of women during childbirth in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative studies conducted in other countries to determine the level and type of D&A show high abuse rates, especially in African countries [8,20]. Few studies were found to assess women's D&A experiences during childbirth [21][22][23][24]. In Iran, no rigorous study was found to use a standard measurement tool to assess and manage RMC.…”
Section: Introductionmentioning
confidence: 99%